Historical references respect to didactic profile of the 18th century music teacher from three European treatises - Lopera Quintanilla, Alejandra (2020)
The profile of the music teacher who could rule in Europe during the first half of the 18th century, including his didactic qualities, general knowledge and musical skills, has not been historically studied in depth. However, a careful reading of three important treatises of the time sheds light on this. Therefore, the main objective of this text is to recognize what the didactic profile of the music teacher was in the first half of the 18th century in Europe, based on a review of three texts of the time and the work of their authors: three composers musically virtuosic and potentially didactic. The historical sources studied in this work are Les principes du clavecin (1702) by the composer Monsieur de Saint Lambert, Versuch einer Anweisung die Flöte traversiere zu spielen (1752) by the virtuoso flutist and composer Johann Joachim Quantz, and Versuch über die wahre Art das Clavier zu spielen (1753) by the composer Carl Philipp Emanuel Bach.